Note on the genus Ovidia - Nevling, L. I.
vol: 13 / no: 1 / p.72-86 / Inv: 06-R00176-ej.1 01-R08812-ej.2 02-R05946-ej.3 / ST: AR-D/1 v 13 no 1____________________________
En: vol 13, no 1
Keywords: Flora; Argentina; Patagonia; Chile; Thymelaeaceae; Ovidia